Made crypto losses? Don't assume the taxman will subsidise you - OOI, Vincent (Institutional Knowledge at Singapore Management University, 2022)
The key points we made in the article are as follows:1) One might think that because income from transactions involving cryptocurrencies is taxable, the losses from such transactions would also be deductible. Unfortunately, the situation is not quite so straightforward.2) The key question is whether it is possible to establish that there was a trade or business (in trading cryptocurrencies). If so, then the deduction rules are a lot more generous. Otherwise, there will be quite a few restrictions:a) Losses from cryptocurrency transactions are unlikely to be useable to be set off against income from other sources.b) The losses will be subject to source-by-source matching requirements, where the losses must be scrupulously matched against each source. This means that one cannot assume that losses from selling Cryptocurrency A can be offset against income from selling Cryptocurrency B in the same year.c) Losses cannot be carried back and set off against income from the same source, such as from selling cryptocurrencies in the previous year, or carried forward and offset against income that might occur in the future by selling cryptocurrencies.3) The position generally taken by the Inland Revenue Authority of Singapore (IRAS) with respect to the buying and selling of shares by individuals is that there is no trade or business. It is likely that this approach will be taken for cryptocurrency as well. Individuals including their cryptocurrency losses in their tax returns this year are likely to find the IRAS unimpressed.It is perhaps more common for cryptocurrency investors to focus on the potential gains rather than the potential losses. However, it is also important to consider the tax implications of potential losses as they can be quite significant as well. A competent tax professional should be consulted before investments are made.